Recontextualizing Asbāb al-Nuzūl: From Micro-Historical Triggers to Macro-Ethical Frameworks within the Qur’anic Hierarchy of Values - Siti Khodijah; Suqiyah Musafa'ah (KURAS Institute, 2025)
The study of asbāb al-nuzūl occupies a strategic position in Qur’anic exegesis as a bridge between the revealed text and its historical context. Classical approaches have often emphasized micro-level triggers, specific events or individuals, resulting in narrow and legalistic interpretations. In contemporary Qur’anic discourse, Abdullah Saeed’s Hierarchy of Qur’anic Values calls for an integration of both micro and macro contextual approaches to produce interpretations that are more ethical and socially relevant. This study employs a qualitative methodology based on literature review and analytical hermeneutics. The analytical framework combines micro-textual analysis with macro-contextual examination, evaluated through the lens of the Hierarchy of Qur’anic Values. A case study of Surah al-Nisa’ verse 3 reveals that this integrative approach enables a dynamic reading of normative verses. Specifically, the verse’s apparent permissibility of polygamy is recontextualized as an ethical directive emphasizing justice for orphans and vulnerable women, rather than as a general legal sanction. The findings demonstrate that asba>b al-nuzu>l should not be treated merely as historical annotations but as a hermeneutical tool for rearticulating the Qur’an’s universal values, such as justice, gender equity, and protection of the marginalized, in contemporary contexts.